Regulation of Aspartokinase Activity in Clostridium perfringens - Kuramitsu, Howard K. (1973)
Cells of Clostridium perfringens type D apparently possess only a single species of aspartokinase. This enzyme has been partially purified and shown to be feedback inhibited by meso-diaminopimelate in an allosteric manner. The inhibitor exerts its action noncompetitively with respect to both substrates. The kinetic analysis further indicates that no homotropic cooperative interactions occur between either multiple substrate or inhibitor sites. Like aspartokinases from other bacteria, the clostridial enzyme is stimulated by the presence of either potassium or ammonium cations. A molecular weight of 102,000 was estimated for the enzyme following gel-filtration chromatography. Enzyme activity remains relatively constant throughout the growth cycle of the organism even well into the stationary growth phase. These results are discussed in terms of the role of the enzyme in the growth of the organism.